2021
DOI: 10.1007/s42398-021-00194-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial agents used in COVID-19: A systematic review and meta-analysis

Abstract: There have been speculations regarding rise in antimicrobial resistance (AMR) globally owing to indiscriminate antibiotic usage during the COVID-19 pandemic. To curb the menace through decisive policies, it is essential to assess the antibiotics, particularly the antibacterial agents. This systematic review and meta-analysis were performed to assess antibiotic use in COVID-19 patients. A thorough systematic search was undertaken in databases like PubMed, Cochrane library, Google Scholar, World Health Organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Cephalosporin and azithromycin were the most commonly used antibacterial prophylactics and treatment against bacterial coinfections in SARS-CoV-2 patients, but there still lack literature on their exact indications and efficacy [ 36 ]. In addition, these antibiotics with antiviral agents were often used without solid microbiological evidence on bacterial coinfections followed by COVID-19 infections in mild to moderate patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cephalosporin and azithromycin were the most commonly used antibacterial prophylactics and treatment against bacterial coinfections in SARS-CoV-2 patients, but there still lack literature on their exact indications and efficacy [ 36 ]. In addition, these antibiotics with antiviral agents were often used without solid microbiological evidence on bacterial coinfections followed by COVID-19 infections in mild to moderate patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, some other clinical trials related to the new drugs for SARS-CoV-2 are still underway [ 33 ]. The combination of antiviral agents and antibiotics was widely used to treat SARS-CoV-2 patients globally in practice, and some existing studies reported efficacy and safety of antiviral agents in SARS-CoV-2 [ 34 , 35 ], but studies on those of antibiotics with solid clinical results are still lacking despite their wide empirical use [ 36 ]. Thus, here we present our experience on SARS-CoV-2 management with pharmacological therapy based on clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings do not support the hypothesis of a protective role of azithromycin in all observed endpoints. Instead, our data outline the concern of potential inappropriate use of this medication, which was empirically prescribed in subjects infected with SARS-CoV-2 during the pandemic period (Gonzalez-Zorn et al, 2021, Sharma et al, 2021, Huang et al, 2020, ECDS 2021. In fact, despite the massive use of antibiotics observed in subjects developing early COVID-19 symptoms (Sharma et al,2021, Khan et al, 2022, several studies have shown that co-infection and secondary bacterial infection occurred only in 3.5%-14.3% of COVID-19 patients (Sharma et al,2021, Lansburry et al, 2020, Langford et al, 2020, Hughes et al, 2020, Chedid et al, 2021, ECDS 2021).…”
Section: Discussionmentioning
confidence: 88%
“…Since the early phase of virus diffusion, several drug classes have been repurposed as potential candidates for COVID-19 treatments, including non-steroidal anti-inflammatory drugs (NSAIDs), glucocorticoids, and heparins (Perico et al, 2020, Sanders et al, 2020. Among others, azithromycin, a second-generation macrolide, received increasing attention because of its antiviral and immunomodulatory activities (Langford et al, 2021, Abdelmalek et al, 2022, Sharma et al, 2021. A body of evidence on the effect of azithromycin on viral infections such as Zika, rhinovirus and Ebola infection contributed to raise the hypothesis of potential efficacy of azithromycin against SARS-CoV-2 infection resulting from multiple possible mechanisms of action (Bosseboeuf et al, 2018, Madrid et al, 2015, Gielen et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…A good number of studies reported high use of antibiotics during COVID-19 on hospitalized and non-hospitalized patients. [20][21][22][23][24][25] These uses were partly due to the clinical care guidelines in some countries. However, Goyal et al reported that out of 393 COVID-19 patients in New York, only 5.6% developed bacteremia without receiving antibiotics.…”
Section: Dovepressmentioning
confidence: 99%